Seasonal dynamics in community structure, abundance, body size and sex ratio in two species of Neotropical annual fishes - Lanés, L E K; Godoy, R S; Maltchik, L; Polačik, M; Blažek, R; Vrtílek, M; Reichard, M (Journal of fish biology, 2016)
Seven ephemeral pools on the coastal plain of southern Brazil were found to be inhabited by three annual and 22 non-annual fish species. Two common annual species (Austrolebias minuano and Cynopoecilus fulgens) exhibited clear seasonal dynamics, with the appearance of young fishes in the austral autumn (May to June) and a decline in abundance over the seasonal cycle. The third annual species, Austrolebias wolterstorffii, was rare. No seasonal dynamics were observed in non-annual fishes. The relative abundance of non-annual fishes compared with annual fishes increased over the seasonal cycle, but they coexisted widely. The size structure of annual fishes suggested the presence of a single age cohort in most pools though a second age cohort was registered in one pool in August, coinciding with a large flooding. Strong sexual dimorphism in body size was found in C. fulgens throughout the seasonal cycle, while no sexual dimorphism in body size was found in A. minuano. Female-biased sex ratios were recorded in both common annual fish species in the last three sampling dates (in spring), but not during the first two sampling dates (in winter). The natural lifespan of annual fishes was <8 months. Annual fishes disappeared before habitat desiccation in half of the pools, while non-annual fishes were still present.
Keywords: Population Density; Animals; velikost těla; Female; Seasons; Lagoa do Peixe; ženské pohlaví; Brazil; coexistence; Body Size; Sex Ratio; Fishes; hustota populace; temporary habitat; roční období; sex-biased mortality; ryby; Sex Characteristics; coastal floodplain; Male; poměr pohlaví; pohlavní dimorfismus; Cyprinodontiformes; Brazílie; ekosystém; Ecosystem; zvířata; mužské pohlaví; life cycle